PENERAPAN GMP DAN PERENCANAAN PELAKSANAAN HACCP (Hazard Analysis Critical Control Point) PRODUK OLAHAN PANGAN TRADISIONAL (Mochi) - Wildan Wibawa Perdana (Fakultas Sains Terapan, Universitas Suryakancana Cianjur, 2018)
HACCP(Hazard AnalyticalCritical ControlPoint/Hazard analysis and critical control points)is a system thatcontrolfood safetystarting fromthe farmtoeatable food.This system emphasizesthe importance ofselectingthe right technology andhowto validatethetechnology.The implementation ofGMP isfollowedin the formofSSOP which areadded value forfoodcompaniesto be ablepenetrate the export market, in accordance withtrade firms of target country.This study aimed toevaluate the condition ofthe basicfeasibility requirementsin line with therequirementsof GMPandHACCP, analyzing the Implementation ofSOPbased onthe critical pointsasaguidance of theimprovement of production processes, Arrangingthe HACCP plandocument(HACCPplan)forproductionas a guidein the implementation ofthe HACCP system, Recommendthe HACCP planforthe development ofHACCP system, andredesignthe layout ofthe facilityafterseeingaspects ofdeviations thatoccurinthe production process.